Measuring patient outcomes - Nolan, Marie T.; Mock, Victoria; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2000)
'Measuring Patient Outcomes' uses the statistical analysis programme SPSS to analyse patient outcomes data and create graphs summarising this data. A series of case studies describing successful patient outcomes projects is included.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Outcome assessment (Medical care); Electronic books